IMPLEMENTATION OF CHATBOT CUSTOMER SERVICE FEATURES ON PT DIAN PRIMA JAYARAYA USING DIALOGFLOW - Putra, Heru Soetanto; Santoso, Hari; Cifran, Cifran (Infotech: Journal of Technology Information, 2022)
The customer service team functions to accommodate questions and answer questions experienced by application users. There are times when the number of questions that are accommodated is so large that the existing customer service team does not handle them. Ignored or unanswered questions can reduce customer satisfaction levels. For this reason, we need a system that can help automate customer service activities so as to avoid unanswered customer questions. A chatbot is a service powered by a set of rules and sometimes artificial intelligence, which interacts with users via a chat interface. Chatbot will be built within the iOS prototype application and will use the Natural Language Processing (NLP) platform, Dialogflow. This platform will later process and scan every question given by the customer so that by implementing this feature the customer service team can work more effectively because some of the manual activities have been automated. The results of this study are that the chatbot system created can reduce the frequency of questions by Solo application users by up to 92.82%. Thus, it is hoped that the customer service team can work more effectively and strategically, and can increase customer satisfaction.